Conceptions and Frameworks: Key Trends on the Rule of Law in Latin America - Aldao, Martin Maria (2023)
Latin America, like the rest of the world, does not escape the apparent tension between a formal and a material concept of the rule of law (second part). The formal concerns with the abuse of public power as shown by the many dictatorships that have plagued the region and the subsequent transitions (third part). The material concerns social conditions, the paradigmatic case being Colombia’s 1991 constitution, but also previous welfare policies and recent constitutional case law (fourth part). Notwithstanding, from the end of the 20th century onwards, the question of frameworks became gradually more relevant in the region: that is to say, neither the formal nor the material conception of the rule of law can be accurately accounted for without its conditions of possibility. Since the 2000s, it has become increasingly clear that it is necessary to question the frameworks of these conceptions as both took for granted that nation-states were the ultimate guarantors of the rule of law. However, in Latin America, states face political, financial, and economic forces (Lasalle 1942) that condition their capacity to guarantee the rule of law. This is why a third trend, complementary to the previous ones, appears (third part). If the state is to guarantee the rule of law, then this requires making these frameworks visible – and accountable. The regulation of global actors and local elites is inseparable from the discussion on both, the formal and the material concepts of the Rule of Law.